2004
DOI: 10.1063/1.1738632
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and electronic structure of Vn(Bz)m complexes

Abstract: First-principles calculations based on the generalized gradient approximation to the density functional theory are performed to explore the global geometries, ground-state spin multiplicities, relative stabilities, and energetics of neutral and anionic V(n)(Bz)(m) (n=1-3, m=1-4, with n Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
181
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(200 citation statements)
references
References 19 publications
17
181
2
Order By: Relevance
“…Our preliminary calculations for both D6h and D6d [V(Bz)] ∞ polymer indicate that the electronic and magnetic properties of the D6d conformer differ little from those of the corresponding D6h one. The qualitative similarity between the D6d and D6h configurations is also found in previous study on the sandwich clusters [14]. So hereafter we mainly focus on the polymers with D6h symmetry.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Our preliminary calculations for both D6h and D6d [V(Bz)] ∞ polymer indicate that the electronic and magnetic properties of the D6d conformer differ little from those of the corresponding D6h one. The qualitative similarity between the D6d and D6h configurations is also found in previous study on the sandwich clusters [14]. So hereafter we mainly focus on the polymers with D6h symmetry.…”
supporting
confidence: 76%
“…A subsequent density functional study confirmed the FM coupling in multidecker sandwich V n (Bz) n+1 clusters [8]. Motivated by the above experimental and theoretical studies, we propose that the 1D organometallic sandwich polymers [V(Bz)] ∞ are the possible candidates for spintronic devices for spinpolarized transport since the polymers with an inherently uniform size are supposed to be also FM.Metal-ligand molecules have been the subject of many studies in the past decade [9,10,11,12,13,14,15,16]. Especially, TM-Bz complexes (M n (Bz) m ) are the prototypical organometallic complexes for studying the d−π bonding interactions.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In the past decade, laser vaporization techniques have provided an alternate route to produce complexes in the gas phase, thus eliminating the need to invoke solvation effects (127)(128)(129)(130). Analysis of mass spectra, reactivity of mass selected species, and dissociation energies, combined with complementary theoretical calculations (131)(132)(133)(134)(135)(136)(137)(138), provide information on atomic and electronic structures. For example, it is possible to determine the sites the metal atoms occupy on the organic molecule, the manner in which metal atoms cluster, and the changes in the structure as multiple organic molecules attach to these complexes.…”
Section: Clusters In Chemistrymentioning
confidence: 99%
“…Cr(Bz) 2 and Mn(Bz) 2 with a sandwich structure are also observed experimentally [61]. Although the multidecker sandwich M n (Bz) m clusters have been extensively studied theoretically [62][63][64][65], studies of the 1D [TM(Bz)] ∞ polymers are still very lacking. To our knowledge, only one semiempirical Hückle calculation was performed to examine the thermodynamical stability of the 1D [TM(Bz)] ∞ polymers [58].…”
Section: Tm-benzene Sandwich Polymersmentioning
confidence: 99%